The most common isolated microorganisms and its clinical manifestation in hospitalised women suffering from urogenital diseases - Naumčiks, Anatolijs; Turoka, Elvīra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The monitoring of genital tract infections, especially sexually transmitted infections, is a vital part of health priority in many countries. One of the most common vaginal infections in women of childbearing age is bacterial vaginosis. Methods: This is a laboratory based retrospective study. We analysed 774 patients’ cases (age range 18-35 years). Patients were subcategorized into three groups: patients with inflammation in genital tract, patients without inflammatory processes in genital tract, threatened abortion women. Laboratory tests also were divided depending on the type of examination. Results: There were 49 patients in the first group, 60 women in the second group and 236 pregnant women with threatened abortion in the third group. Gram negative bacteria (Escherichia coli and Enterococcus spp.) were the most common isolated bacteria in the first and second group. Coagulase-negative staphylococci were predominant in the third group. Streptococcus agalactiae was isolated in 11.8 % cases. In our study, Trichomonas vaginalis infection was found in 1.2%. Conclusions: The most common isolated bacteria were Coagulase-negative staphylococci and gram negative bacteria. Ureaplasma urealyticum was detected in a decisive majority (38.9%) of Mycoplasma species infections. In the first patients group – women with inflammatory process in genital tract were not found 3 bacteria, opposite to the second and third group.